Pandemic-Related Experiences and Psychosocial Risk Associations Among U.S. Medical Students - Nathaniel A. Jenkins; Damion J. Grasso (International Journal of Medical Students, 2022)
Background: Since the start of the COVID-19 global pandemic there has been a profound impact on the psychosocial health of medical professionals, with heightened risk reported on measures of depression, anxiety, and stress relative to non-healthcare professionals. However, there is limited data on the impact of COVID-19 on the psychosocial health of U.S. undergraduate medical students. The current cross-sectional study aims to examine associations between pandemic-related experiences and psychosocial risk among a sample of medical students attending a Northeastern U.S. allopathic medical school. Methods: One-hundred and seventy-nine students (42.6% of the study body) completed an online survey during the COVID-19 pandemic that included sociodemographic characteristics, the 30-item Brief Epidemic-Pandemic Impacts Inventory (EPII-B), the 2-item Patient Health Questionnaire (PHQ-2), the 2-item Generalized Anxiety Disorder (GAD-2), and the Primary Care PTSD Screen for DSM-5 (PC-PTSD-5). Results: Rates of serious adverse pandemic-related experiences (e.g., increased conflict, less physical activity, frequent substance use) were as high as 37.5%. Students with a greater number of adverse pandemic-related experiences reported more time with COVID-19 positive patients and were more likely to screen positive for depression, anxiety, and PTSD (rs from 0.25 – 0.34, all ps < 0.01). Conclusion: These findings suggest the need for other U.S. medical schools to evaluate and address medical student mental health during the COVID-19 public health crisis.